Endometrial Stromal Nodule: Report of a Case - F. Z. Fdili Alaoui; H. Chaara; H. Bouguern; M. A. Melhouf; H. Fatemi; A. Belmlih; Afaf Amarti (Case Reports in Medicine)
Endometrial stromal nodule (ESN) is the least common of the endometrial stromal tumors. They are rare neoplasms which are diagnosed in most instances by light microscopy. Although such nodules are benign, hysterectomy has been considered the treatment of choice to determine the margins of the tumor required for diagnosis and to differentiate it from invasive stromal sarcoma Whose prognosis is totally different. We report a case of a 45 years old woman, with presurgical diagnosis of adnexal mass or uterine tumor. She underwent a total abdominal hysterectomy. Pathologic examination revealed an endometrial stromal nodule. Through this observation, we insist on the fact that the ESNs are rare and benign entities which must be differentiated from the other invasive malignant stromal tumors; this can change the final prognosis.